Differential Diagnostic Value of Histology in MPLC and IPM: A Systematic Review and Meta-Analysis - Tian, Sen; Li, Fuqi; Pu, Jin; Zheng, Yi; Shi, Hui; Dong, Yuchao; Chen, Ruohua; Bai, Chong (Frontiers in Oncology, 2022)
Background The paramount issue regarding multiple lung cancer (MLC) is whether it represents multiple primary lung cancer (MPLC) or intrapulmonary metastasis (IPM), as this directly affects both accurate staging and subsequent clinical management. As a classic method, histology has been widely utilized in clinical practice. However, studies examining the clinical value of histology in MLC have yielded inconsistent results; thus, this remains to be evaluated. Here, we performed a meta-analysis to assess the differential diagnostic value of histology in MPLC and IPM and to provide evidence-based medicine for clinical work. Methods PubMed, Embase, and Web of Science databases were searched to collect relevant literature according to PRISMA, and inclusion and exclusion criteria were set up to screen and assess the literature. The data required for reconstructing a 2 × 2 contingency table were extracted directly or calculated indirectly from the included studies, and statistical analysis was carried out by using Stata 15, Meta-DiSc 1.4, and Review Manager 5.4 software. Results A total of 34 studies including 1,075 pairs of tumors were included in this meta-analysis. Among these studies, 11 were about the M-M standard and the pooled sensitivity and specificity were 0.78 (95% CI: 0.71–0.84) and 0.47 (95% CI: 0.38–0.55), respectively; 20 studies were about CHA and the pooled sensitivity and specificity were 0.76 (95% CI: 0.72–0.80) and 0.74 (95% CI: 0.68–0.79), respectively; and 3 studies were about the “CHA & Lepidic” criteria and the pooled sensitivity and specificity were 0.96 (95% CI: 0.85–0.99) and 0.47 (95% CI: 0.21–0.73), respectively. The combined pooled sensitivity, specificity, PLR, NLR, DOR, and the area under the SROC curve of the 34 studies were 0.80 (95% CI: 0.73–0.86), 0.64 (95% CI: 0.51–0.76), 2.25 (95% CI: 1.59–3.17), 0.31 (95% CI: 0.23–0.43), 7.22 (95% CI: 4.06–12.81), and 0.81 (95% CI: 0.77–0.84), respectively. Conclusion The current evidence indicated that histology had a moderate differential diagnostic value between MPLC and IPM. Among the three subgroups, the “CHA & Lepidic” criteria showed the highest sensitivity and CHA showed the highest specificity. Further research is necessary to validate these findings and to improve clinical credibility. Systematic Review Registration PROSPERO, identifier CRD42022298180.